PRINCIPLES OF EDUCATION CONTENT SELECTION IN THE CONTEXT OF FUNDAMENTALIZATION - Захарчук, Н. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The article considers one of the most important issues of the theory of education nowadays - the problem of selection of education content in secondary and higher education. The author analyzes outlined problem in the course of the current process of curriculum fundamentalization. The article aims to offer relevant principles of systematization and selection of education content, compliance with which will ensure optimal organization and conduct of educational work in fundamentalizational processes. The paper proposes the principles of selection of education content, to which the author adds orientation of education content on the functional use of the obtained knowledge (profile / professional knowledge orientation, their practical significance); implementation of education content selection taking into account fundamental nature of knowledge (the ability to acquire new knowledge from already obtained); modern character of knowledge, that meets the requirements of society and reflects the today’s situation; orientation of educational content on the formation of personal values